2001
DOI: 10.1097/00012272-200112000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Reinvesting in Social Justice: A Capital Idea for Public Health Nursing?

Abstract: Social justice is a core ethical principle of public health nursing; yet, nurses' work as social activists has largely diminished over the past century. Reengagement in social justice activities is essential to change the current social, economic, and health differentials perpetuated by market justice ideologies. Social capital has emerged in the public health literature as a promising concept for developing community interventions that diminish disparities. Public health nurses, however, must be wary of uncri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 26 publications
0
77
0
Order By: Relevance
“…Stevens and Hall (1992) described citizen participation as an egalitarian partnership between professionals and lay persons, groups, and communities that consider issues of social justice and equity that are inherent in primary health care. In their reflective article, Drevdahl, Kneipp, Canales and Dorcy (2001) reminded readers that public health nurses' historical practice has been to advocate for a healthy society through social justice.…”
Section: Discussionmentioning
confidence: 99%
“…Stevens and Hall (1992) described citizen participation as an egalitarian partnership between professionals and lay persons, groups, and communities that consider issues of social justice and equity that are inherent in primary health care. In their reflective article, Drevdahl, Kneipp, Canales and Dorcy (2001) reminded readers that public health nurses' historical practice has been to advocate for a healthy society through social justice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although epidemiologic research had shown a statistically significant association between social capital and health (Kawachi, Kennedy, & Glass, 1999;Kawachi, Kennedy, Lochner, & Prothrow-Stith, 1997), the association was statistically insignificant for the African American population. Furthermore, a number of public health practitioners were strongly advocating against the uncritical adoption of social capital as a focus for research or policy formation (Drevdahl, Kneipp, Canales, & Dorcy, 2001;Lynch, Due, Muntaner, & Smith, 2000). However, these findings and critiques were not congruent with the experience and observations of EDC.…”
Section: A Case Studymentioning
confidence: 99%
“…Though many definitions of social justice are proposed, it can be viewed as the equalizing of the balance of societal burdens and benefits (Beauchamp, 1986, Drevdahl, Kneipp, Canales & Dorcy, 2001Whitehead, 1992). This definition recognizes that there are societal rights and collateral responsibilities which make everyone accountable for action (Lebacqz, 1986).…”
Section: Literature Review: Social Justice and Baccalaureate Nursing mentioning
confidence: 99%
“…Despite the definitional critiques, social justice is still espoused as a central value for community health nurses in the US (Drevdahl, Kneipp, Canales & Dorcy, 2001). Community health nurses often encounter justice issues from population and community based perspectives.…”
Section: Literature Review: Social Justice and Baccalaureate Nursing mentioning
confidence: 99%